FLAT : federated lightweight authentication for the internet of things - Henriques, Marco Aurelio Amaral, 1963- (2020)
Agradecimentos: We would like to thank Michelle Wangham, André Lins, Clayton Reis, Artur Souza, Antônio Maia, Pedro Pinto, Emerson Mello, and Mark Horowitz for contributing with fruitful discussions to this work. We also thank RNP for funding the work group GT-CoFee, and CNPq for funding the process 306472/2017-1, and FAPEMIG for funding the process APQ-02990-15. This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001